2017
DOI: 10.3889/oamjms.2017.151
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression in Epithelial and Stromal Cells of Prostatic Carcinoma and Benign Prostatic Hyperplasia

Abstract: BACKGROUND:Prostatic carcinoma (PCa) derives from prostatic epithelial cells. However stromal microenvironment, associated with malignant epithelium, also plays a role in prostatic carcinogenesis. Alterations in prostatic stromal cells contribute to the loss of growth control in epithelial cells that lead to progression of PCa.AIM:To analyse the differences between Androgen Receptor (AR) expression in both epithelial and stromal cells in PCa and the surrounding benign prostatic hyperplasia (BPH) and to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…For example, some count nuclear staining or measure overall staining, others compare stromal vs. epithelial or primary cancer vs. metastasis. Several studies have, however, reported an inverse relationship between AR protein expression and Gleason grade, particularly when comparing stromal tissue to epithelial cells [42][43][44]. The current study did not differentiate between the stromal and epithelial compartments and the IRS for AR is significantly lower in all pathologies compared to normal prostate.…”
Section: Discussioncontrasting
confidence: 84%
“…For example, some count nuclear staining or measure overall staining, others compare stromal vs. epithelial or primary cancer vs. metastasis. Several studies have, however, reported an inverse relationship between AR protein expression and Gleason grade, particularly when comparing stromal tissue to epithelial cells [42][43][44]. The current study did not differentiate between the stromal and epithelial compartments and the IRS for AR is significantly lower in all pathologies compared to normal prostate.…”
Section: Discussioncontrasting
confidence: 84%
“…Scoring of intensity and percentage positivity was carried out separately. 4,5 Staining intensity was scored from 0-3 as shown in Figures 1, 2 and 3. Where staining intensity is graded as 0= not detectable, 1= translucent, 2= opaque, 3= solid.…”
Section: Methodsmentioning
confidence: 99%
“…Where staining intensity is graded as 0= not detectable, 1= translucent, 2= opaque, 3= solid. 4,5 The percentage of cells staining positively at each level of staining intensity was calculated. We used total staining score, defined as the sum of the percentage of any cells that are staining positively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations